Azimuth from Observations of Close Circumpolar Stars - Bhattacharji, J. C. (The International Hydrographic Review, 2018)
In this paper suggestions have been made to modify considerably the existing time-azimuth and altitude-azimuth formulae to obtain more easily and quickly the first-order and second-order azimuths from observations of close circumpolar stars using lesser numbers of figures in both logarithmic and machine computations with the help of some small correction tables only. A simple chart has also been designed in order to read immediately from the chart third-order or less precise azimuths from observations of the above stars without recourse to elaborate computations. First-order azimuths are used in geodetic surveys while second-order and third-order azimuths have ample applications in topographic and hydrographic surveys including navigation.